Ultrasound, Dacryocystorhinography and Morphological Examination of Normal Eye and Lacrimal Apparatus of the Donkey (Equus asinus) - Ahmed Abdelbaset-Ismail; Mohamed Aref; Shimaa Ezzeldein; Eslam Eisa; Mudasir Bashir Gugjoo; Ahmed Abdelaal; Hassan Emam; Khalid Al Syaad; Ahmed Ezzat Ahmed; Ali Alshati; Mustafa Abd El Raouf (Animals, 2022)
The study investigated normal macromorphological and ultrasonographic features of the eye and lacrimal gland, as well as normal dacryocystorhinography of the donkey (Equus asinus) in Egypt. A total of 36 donkeys of different ages, weights, and sexes were included in the study: 21 live animals for ultrasonography and dacryocystorhinography, and 15 cadaver skulls for morphological anatomy of the lacrimal apparatus. The ultrasound biometric values of the eye were 33.7 ± 1.7 mm for axial globe length (AGL), 39.8 ± 2.1 mm for globe diameter (GD), 10.8 ± 0.7 mm for lens thickness (LT), 3.2 ± 0.7 mm for anterior chamber depth (ACD), and 19.3 ± 1.6 mm for vitreous chamber depth (VCD). The lacrimal gland was recognized as a hypoechogenic structure with an anechoic core, located at the dorsolateral aspect of the orbit, and ovoid in shape. The mean NLD length was 193.0 ± 9.8 mm by radiography and 206.0 ± 20.4 mm by gross assessment. One NL orifice (NLO) was noticed on each side, with a diameter of 3.0 ± 0.1 mm and located 12.1 ± 2.1 mm from the dorsal commissure of the nostril. These results may act as the baseline for proper management of conditions of the eye and lacrimal apparatus in the donkey in the future.